On the development of animal models for degenerative retinal disease - McNally, Niamh (Trinity College (Dublin, Ireland). Department of Genetics, 2000)
Retinitis pigmentosa (RP) is one of the leading causes of inherited blindness within the working population of many developed countries. There is presently no cure for this disorder. The projects outlined in this thesis were undertaken in an attempt to generate and analyze mouse models with RP. Such models are centrally important to the development of methods for the prevention of the disease, as they provide a means to investigate the pathophysiology of the disorder and systems in which to begin assessing retinal therapies. A major objective of this thesis was the development, on site, of procedures for the maintenance and growth of embryonic stem (ES) cells, their genetic manipulation, and the generation by gene targeting of a mouse model for autosomal dominant retinal degeneration. Specifically a 1bp deletion (CTG to C-G) at codon 307 of the mouse peripherin gene was successfully carried out in R1 embryonic stem cells. These cells were used to generate 21 chimeric mice carrying the targeted deletion. To date, two of these mice have passed the 3codon 307 mutation on to the next generation, demonstrating germline transmission of the cell line. In man, the codon 307 mutation within the RDS-peripherin gene results in a slowly progressive form of adRP. A similar phenotype may be produced in mice. If so, these animals would provide a valuable model for dominant disease. The relatively slow retinopathy may possibly provide a broader window of time to realise the potential of certain gene therapy vectors (i.e AAV). Animals carrying a targeted disruption of the rhodopsin gene, (rho-/-), are currently used in studies to evaluate various potential gene therapies as a means to treat human retinal disease. Histopathological, immunocytochemical and electrophysiological data are presented demonstrating substantial structural and functional rescue of rod cells in rho-/- mice retinas. This rescue was brought about by crossing these animals onto a transgenic strain of mouse expressing human rhodopsin. Such information is required for optimal use of Rho-/- mice in exploring methods for suppressing human degenerative retinal conditions whose molecular pathologies are based either upon loss of rhodopsin gene function or on the manifestation of dominant mutations.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin